Teaching-Learning Based Algorithm for Numerical Dynamic Multi-Objective Optimization Problems - Elsawi, Salwa Elsayed Mohamed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
Teaching–Learning-Based Optimization (TLBO) algorithm has become an alternative optimization method in a great number of applications in different fields of engineering and science since it has been introduced in 2011. Teaching-learning-based optimization (TLBO) is a population-based metaheuristic examination algorithm stimulated by the teaching and learning procedure in a classroom environment. TLBO with its comparatively reasonable performances outperforms some of the well-known metaheuristics concerning constrained benchmark tasks, controlled mechanical schemes, and nonstop non-linear numerical optimization problems. In the TLBO algorithm’s variants, all the learners have an equal chance of receiving information from the teacher and from each other as learners by interacting with each other in the class. The Experimental results of the TLBO method are tested on the set of CEC2018 dynamic multi-objective optimization benchmark problems and the computed results show that TLBO offers promising outcomes with diverse dynamic features and changing environments compared with other algorithms. It works well with producing a good class of population when alterations happen for pursuing the influential Paretooptimal set efficiently for refining population conjunction and multiplicity. TLBO extracted improved or equal quality solutions compared to other evolutionary algorithms. It is a promising alternative for the solution of difficult dynamic multiobjective optimization problems.

ÖZ: Öğretme-Öğrenme Tabanlı Optimizasyon (TLBO) algoritması, 2011 yılında tanıtıldığından beri mühendislik ve bilimin önemli sayıdaki farklı alanlarında altenatif bir optimizasyon yöntemi olmuştur. Öğretme-öğrenme tabanlı optimizasyon (TLBO), sınıf ortamında öğretme ve öğrenme süreci üzerine kurgulanan popülasyon tabanlı bir metasezgisel arama algoritmasıdır. Karşılaştırmalı makul başarımlarıyla TLBO, kısıtlamalı kalite testi problemleri, kontrollü mekanik şemalar ve kesintisiz doğrusal olmayan sayısal optimizasyon problemlerinin çözülmesinde iyi bilinen bazı metasezgisel yöntemlerden daha üstün başarım göstermektedir. TLBO algoritmasının değişik uygulamalarında, tüm öğrenenler sınıfta birbirleriyle etkileşime girerek öğretmenden ve birbirlerinden eşit bilgi alma şansına sahiptirler. TLBO yönteminin deneysel sonuçları, CEC2018 konferansında yayınlanan dinamik çok amaçlı kalite testi optimizasyon problemleri kümesi üzerinde sınanmıştır ve hesaplanan sonuçlar TLBO'nun diğer algoritmalara kıyasla çeşitli dinamik özellikler ve değişen ortamlarla umut verici sonuçlar sunduğunu göstermektedir. Problem koşulları değiştiğinde, algoritma iyi bir nüfus yapısı ve çeşitliliği sağlayarak Pareto-optimal çözümler kümesini verimli bir şekilde takip eder. TLBO’nun başarımı diğer evrimsel algoritmalarla karşılaştırıldığında iyileştirilmiş veya aynı kalitede çözümler elde ettiği görülür. Algoritma zor dinamik çok amaçlı optimizasyon problemlerinin çözümü için iyi bir alternatiftir.
Master of Science in Computer Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2023. Supervisor: Assoc. Prof. Dr. Adnan Acan.
Keywords: Thesis Tez; Computer Engineering Department; Artificial Intelligence; Optimization Problems; Dynamic Multi-Objective Optimization Problems; Optimization Algorithms; Teaching Learning Based Optimization; Pareto-Front; Pareto-Set